2023
DOI: 10.18632/aging.204487
|View full text |Cite
|
Sign up to set email alerts
|

Selective ATM inhibition augments radiation-induced inflammatory signaling and cancer cell death

Abstract: Over half of all cancer patients undergo radiation therapy but there is an unmet need for more efficacious combination strategies with molecular targeted drugs. DNA damage response has emerged as an important intervention point for improving anti-tumor effects of radiation and several inhibitors are currently in development. Ataxia telangiectasia mutated (ATM) kinase is a key regulator of cellular response to DNA double strand breaks and a potential target for radiosensitization. We recently reported two new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…DDR inhibitors accelerate the production of micronuclei in the nucleus, which is an important factor in dsDNA production. The production of dsDNA activates the cGAS-STING-TBK1-IRF3 signaling pathway and promotes the release of type I IFN ( Chiu et al, 2023 ). Meanwhile, DDR-related inhibitors promote the SUMO-ization of SHP1 at lysine 127, inhibiting the TRAF6-STING-p65 signaling pathway and activating the nonclassical STING signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DDR inhibitors accelerate the production of micronuclei in the nucleus, which is an important factor in dsDNA production. The production of dsDNA activates the cGAS-STING-TBK1-IRF3 signaling pathway and promotes the release of type I IFN ( Chiu et al, 2023 ). Meanwhile, DDR-related inhibitors promote the SUMO-ization of SHP1 at lysine 127, inhibiting the TRAF6-STING-p65 signaling pathway and activating the nonclassical STING signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Many preclinical trials have been conducted to explore the mechanism of the combined application of ATM inhibitors and ICIs to enhance the efficacy of immunotherapy. The application of ATM inhibitors to tumor cells blocks ATM signaling in tumor cells, leading to the inability to activate the G1/S cell cycle checkpoint and massive tumor cell death ( Chiu et al, 2023 ). ATM inhibitors lead to defective DNA damage repair, which in turn induces chromosomal instability and abnormal division, forming micronuclei.…”
Section: Preclinical and Clinical Trials Of Ddr Inhibitors In Combina...mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings highlight the complex interplay of chemotherapy with the cGAS-STING pathway 96 . Additionally, ATM kinase, a regulator of DNA damage responses, plays a major role in cGAS-STING activation, and ATM inhibitors have shown potential in enhancing cancer cell sensitivity to radiation and promoting interferon responses via the cGAS-STING/TBK1 pathway 30 , 97 .…”
Section: Strategies For Harnessing the Cgas-sting Pathway In Cancer T...mentioning
confidence: 99%
“… 23 In addition, ATM inhibition on irradiated tumor cells showed mitotic disruption, STING pathway activation, and programmed death-ligand 1 (PD-L1) expression in tumors. 24 Furthermore, another group reported that combined radiation and ATM inhibition showed increased CD8+T cell infiltration, decreased CD4+T cell infiltration, and PD-L1 induction in tumor-associated macrophages. 25 These previous reports suggest a capacity for ATM inhibition to modulate the immunogenic effects of radiation within the tumor microenvironment, however further investigation is needed to clarify the mechanisms of this interaction.…”
Section: Introductionmentioning
confidence: 99%